2013
DOI: 10.1186/1471-2229-13-70
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide identification and functional analyses of calmodulin genes in Solanaceousspecies

Abstract: BackgroundCalmodulin (CaM) is a major calcium sensor in all eukaryotes. It binds calcium and modulates the activity of a wide range of downstream proteins in response to calcium signals. However, little is known about the CaM gene family in Solanaceous species, including the economically important species, tomato (Solanum lycopersicum), and the gene silencing model plant, Nicotiana benthamiana. Moreover, the potential function of CaM in plant disease resistance remains largely unclear.ResultsWe performed genom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
63
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(69 citation statements)
references
References 34 publications
3
63
0
1
Order By: Relevance
“…These results revealed that the orthologous expansion of these subfamily members is highly restricted, especially in group I, which may possess more conserved functions. Interestingly, all CaM genes in pear were disrupted by the first intron at the Gly26 codon, which has been previously reported in Arabidopsis and solanaceous CaMs [7, 26]. The majority of the first intron is located in the region of the EF-hand 1, while the second exon encodes multiple EF-hands (Figure 2).…”
Section: Resultssupporting
confidence: 53%
See 1 more Smart Citation
“…These results revealed that the orthologous expansion of these subfamily members is highly restricted, especially in group I, which may possess more conserved functions. Interestingly, all CaM genes in pear were disrupted by the first intron at the Gly26 codon, which has been previously reported in Arabidopsis and solanaceous CaMs [7, 26]. The majority of the first intron is located in the region of the EF-hand 1, while the second exon encodes multiple EF-hands (Figure 2).…”
Section: Resultssupporting
confidence: 53%
“…Due to the multiple functions of CaMs and the increase in the availability of sequenced plant genomes, many CaM genes have been identified at the whole genome level in several plant species including Arabidopsis [5, 7], rice [25], and several species in the Solanaceae family [26]. Pear ( Pyrus bretschneideri ), a species within Rosaceae, is cultivated worldwide as a fruit tree, whose growth, development, and productivity are frequently affected by abiotic stress, such as salinity and drought [27].…”
Section: Introductionmentioning
confidence: 99%
“…Transient over-expression of Capsicum annuum calmodulin 1 ( CaCaM1 ) activated the ROS burst and NO generation, and it induced HR-like cell death in pepper leaves (Choi et al, 2009). Silencing of Solanum lycopersicum SICaM2 and SICaM6 resulted in reduced resistance to Tobacco rattle virus and the oomycete pathogen, Pythium aphanidermatum , via VIGS (Zhao et al, 2013). Accordingly, we transiently expressed five FvCaM and FvCML genes in N. benthamiana leaves and exposed them to both the presence (Ca 2+ treatment) and absence (EGTA treatment) of Ca 2+ .…”
Section: Discussionmentioning
confidence: 99%
“…Real-time quantitative PCR (RT-qPCR) was carried out using SYBR Premix Ex Taq (TakaRa, China) on StepOne Real-Time PCR System (ABI, USA).The RT-qPCR analyses were conducted three times, with three replicates for each gene and the relative fold changes were calculated using the 2 −ΔΔCt method as described (Zhao et al, 2013). A B. napus elongation factor gene was used as the reference gene and primers used for RT-qPCR are listed in Table S2.…”
Section: Methodsmentioning
confidence: 99%